2017
DOI: 10.26905/jkdp.v21i4.1521
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Dividend Policy: A Study of Financial Industry in Indonesia

Abstract: Dividend policy is still a controversial issue and often debated in the literature of corporate finance. Previous literature has examine that companies pay dividend is to attract investors to buy their companies shares. The question, what are the determinants of the company's dividend policy? The purpose of this study is to find out the determinants of dividend policy in financial industry listed in Indonesia Stock Exchange. This study use a panel data analysis method to investigate the determinants of dividen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 36 publications
3
9
0
9
Order By: Relevance
“…Empirical relationships that have been carried out in Europe confirmed that the dividend payments have a positive and significant effect. This was found in research (Skinner & Soltes, 2009;Isakov & Weisskopf, 2015;Crane et al, 2016) Whereas for empirical studies in Indonesia, it has been carried out previous research (Taungke & Supramono, 2015;Gusni, 2017) which also confirmed the same results. Therefore, the third empirical proposition based on the TOT theory is: H3: Dividend is positively related to firm value.…”
Section: The Effect Of Dividend On Firm Valuesupporting
confidence: 80%
“…Empirical relationships that have been carried out in Europe confirmed that the dividend payments have a positive and significant effect. This was found in research (Skinner & Soltes, 2009;Isakov & Weisskopf, 2015;Crane et al, 2016) Whereas for empirical studies in Indonesia, it has been carried out previous research (Taungke & Supramono, 2015;Gusni, 2017) which also confirmed the same results. Therefore, the third empirical proposition based on the TOT theory is: H3: Dividend is positively related to firm value.…”
Section: The Effect Of Dividend On Firm Valuesupporting
confidence: 80%
“…According to Tyastari et al (2017), the dividend policy of a company becomes a matter of great concern to investors. Increasing the dividend policy paid can be a positive signal for investors to provide a good prospect assessment of a company that will affect the interest of investors to buy shares of the company (Gusni, 2017). This will affect the increase in stock price of the company (R. .…”
Section: Discussionmentioning
confidence: 99%
“…The stock price volatility in addition to being influenced by the dividend payout ratio (DPR) of a company is also influenced by the financial performance of the company itself (Gusni, 2017). Skinner and Soltes (2009); Suharli (2007) argues that companies with good financial performance will be more attractive to investors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian yang dilakukan oleh Forti et al (2015), Khan et al (2013) danMalik et al (2013)menemukan bahwa profitabilitas secara positif signifikan mempengaruhi kebijakan dividen. Namun terdapat hasil penelitian berbeda yang ditemukan oleh Gusni (2017), Kaźmierska-Jóźwiak (2015) danOsegbue et al…”
Section: Pendahuluanunclassified